Comparing The Performance of SITH VCO Body Balm to Body Butter Using Blind-Test Method - Sari, Rininta; Iskandar, Budi Permadi (Journal of Business and Management, 2012)
This research tries to compare the performance of SITH VCO body balm to The Body Shop butter using blind-test method.Purpose: To identify the advantages of SITH VCO Body Balm, so that the management will have a clearer target market.Design/methodology/approach: This research use blind-test method, which participated by 98 respondents.Findings: SITH VCO Body Balm has an absolute advantages towards all four tested variables (sensation after sweat, moisture on dry skin areas, absorption, and smell after usage).Research limitations/implications (if applicable): Data only taken in Jabodetabek and Bandung area, this research conducted between June â€“ August 2012, more specifically to those who have dry-skin, and for woman who at least 19 years old. There are also 18 respondents who are refused to do blind-test.Practical implications (if applicable): This research will help the management of SITH VCO body balm to determining the appopriate marketing strategy as a part of product commercialization effort.Â Originality/value: in this reserach, the sample is directly come from the factory. It means this research cam be implemented to the factory that produce this productKeywords-component; Marketing, Blind-test